A bibliography of L.E.J. Brouwer - Dalen, D. van (My University, 1997)
Bibliography of Luitzen Egbertus Jan Brouwer (1881-1966). The list contains not only the scientific papers that appeared in journals of in book form, but also his contributions to newspapers, magazines, etc.
Keywords: Wijsbegeerte